Dog and Bear : three to get ready - Seeger, Laura Vaccaro (Roaring Brook Press, 2009)
Bear has a bucket stuck on his head, but luckily, Dog has a plan. It's not a perfect plan, but in this and two other stories, imperfect plans still work out when good friends help each other.